Unstable Credit Correlations. Issue 74 (November 2014) - Osband, Kent
<x xml:space="preserve">Abstract</x> Credit spreads are typically more correlated than fundamentals warrant because observers can't fully identify differences. However, significant asymmetries in default rates cause spreads to diverge. As a result, credit hedges often fail when most needed.